Consistency of aquatic enclosed experiments: The importance of scale and ecological complexity. Issue 3 (17th December 2020) - Paiva, Filipa; Brennecke, Dennis; Pansch, Christian; Briski, Elizabeta
Abstract: Aim: Marine and freshwater ecosystems are increasingly threatened by human activities. For over a century, scientists have been testing many biological, chemical and physical questions to understand various ecosystems and their resilience to different stressors. While the majority of experiments were conducted at small‐scale laboratory settings, lately large mesocosm experiments have become more and more common. Yet, it still remains unclear how the scale (i.e. space) and ecological complexity (i.e. community versus limited number of species) of experiments affect the results and to what extent different experimental types are comparable. Innovation: Here, we conducted two types of experiments, run at different scale and ecological‐complexity levels (i.e. outdoor large‐scale community‐level mesocosm versus indoor small‐scale two‐species laboratory experiment), to assess the effects of marine heatwaves on two gammarid species. Main Conclusions: Our approach detected differences in abundance and relative population growth between the two experimental types for one out of the two tested species, but no difference in heatwave impacts on any of the species, independently of which experimental type was used. The larger space in the mesocosm, accompanied with inclusion of the community, benefited this species, demonstrating stronger performance in the mesocosm than in the laboratory experiment. Though, our study design cannot directly distinguish if scale or ecological complexity of the experiments, or both, caused the observed discrepancy in our findings. Furthermore, inconsistency in results among laboratory experiments complicates the extrapolations and generalization of the laboratory results. Yet, our findings indicate the importance of space, density‐dependent effects, biotic interactions and complexity of natural environments in buffering, or boosting, the direct effects of environmental stress on organisms. Therefore, we urge the use of large‐scale community‐level mesocosm experiments instead of small‐scale single‐species laboratory ones whenever possible, and emphasize a necessity of great caution when interpreting the results of laboratory experiments.